2019
DOI: 10.1002/adsc.201900922
|View full text |Cite
|
Sign up to set email alerts
|

Rhodium‐Catalysed [4+2] Annulation of Aromatic Oximes with Terminal Alkenes by C−H/N−O Functionalization towards 3,4‐Dihydroisoquinolines

Abstract: Rhodium (Rh)-catalysed [4 + 2] annulation of aromatic oximes with common terminal alkenes for the synthesis of 3,4-dihydroisoquinolines is presented. Through the cooperation of a Rh (III) catalyst and a catalytic amount of K 2 HPO 4 base, the reaction enables the formation of two new bonds, a C(sp 2 )À C(sp 3 ) bond and a C(sp 3 )À N bond, in a single reaction via functionalization of both the CÀ H and NÀ O bonds and provides a practical method to produce 3,4-dihydroisoquinolines with exquisite selectivity and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…[203] The above method was later improvised by Zhang et al by eliminating the need of additive to synthesize 3,4-dihydroisoquinolines 105 in good yields (Scheme 199). [204] Wang et al [205] Chu et al [206] and Lin et al [207] have developed a similar Rh-catalyzed annulation of benzylamines and diazo compounds. He et al have demonstrated Rh-catalyzed intramolecular reaction of bromonium ylides, which are obtained upon reaction of benzyl bromide 333 and αimino carbene to access 4-bromo-1,2-dihydroisoquinolines 334 (Scheme 201).…”
Section: Rh-catalyzed Isoquinoline Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…[203] The above method was later improvised by Zhang et al by eliminating the need of additive to synthesize 3,4-dihydroisoquinolines 105 in good yields (Scheme 199). [204] Wang et al [205] Chu et al [206] and Lin et al [207] have developed a similar Rh-catalyzed annulation of benzylamines and diazo compounds. He et al have demonstrated Rh-catalyzed intramolecular reaction of bromonium ylides, which are obtained upon reaction of benzyl bromide 333 and αimino carbene to access 4-bromo-1,2-dihydroisoquinolines 334 (Scheme 201).…”
Section: Rh-catalyzed Isoquinoline Synthesismentioning
confidence: 99%
“…by eliminating the need of additive to synthesize 3,4‐dihydroisoquinolines 105 in good yields (Scheme 199). [204] …”
Section: Synthesis Of Isoquinoline Derivativesmentioning
confidence: 99%
“…[21][22][23] During the preparation of this manuscript, the group of Chen and Li reported the reaction of aromatic oximes with various styrenes to give dihydroisoquinoline heterocycles (Scheme 1, equation E). 24 However, similar reactions with aliphatic alkenes remained unexplored.…”
Section: Letter Syn Lettmentioning
confidence: 99%
“…On the other hand, 3,4-dihydroisoquinolines (DHIQ) as an inactivated cyclic imine have been broadly applied as valuable synthons which could react with nucleophilic reagent to fulfill potential active tetrahydroisoquinoline derivatives in organic synthesis [69][70][71][72][73][74][75][76]. In 2017, the Cui and co-workers developed catalyst-free [3 + 2] cyclization of 3,4-dihydroisoquinolines and aldehydes-derived MBH carbonates to provide tetrahydropyrroloisoquinolines in good yields (Scheme 1a) [77].…”
Section: Introductionmentioning
confidence: 99%